ANALYSIS OF THE IMPACT OF INSTALLING CAI AND IMS ON A MOTORCYCLE ENGINE - Wijianto, Wijianto; Sarjito,; Subroto,; Faishal, Afif; Supriyono,; Anam, Choirul (Journal of Applied Engineering Science, 2025)
Engine performance and fuel efficiency are very important in a motor vehicle, so many studies aim to improve the performance of motor vehicles. The Intake Manifold Spacer (IMS) is placed on the intake manifold channel before the air and fuel mixture enters the combustion chamber, while the Cyclonic Air Injector (CAI) is placed on the air channel that will enter the carburettor chamber. With the addition of IMS and CAI, it is expected to increase the homogeneity of the fuel-air mixture and provide a turbulent flow effect (swirling) on the air entering the carburettor and the air-fuel mixture entering the combustion chamber. The method used in this study is to manufacture IMS and CAI with variations in the number of blades: 3 and 4 and the angle of inclination of the blades 35o and 45o. Testing was conducted on a 110cc 4-stroke motorcycle, where a dyno test was used to determine power, torque, and fuel consumption. The results of this study show that the addition of IMS and CAI can improve performance and increase fuel efficiency compared to standard motor vehicle conditions. The largest increase in motor power was in the variation of adding IMS and CAI with 4 blades and a blade angle of 35o, which was 3.9%. Meanwhile, the maximum torque increased by 3.9 in the variation of adding IMS and CAI with 4 blades and a blade angle of 45o. Fuel consumption also experienced savings or decreased compared to the standard conditions of all test variations. The highest efficiency of 9.36% occurred in the variation of adding IMS. Based on this research, it can be one of the considerations to improve the performance of combustion engines for the automotive industry. It can also serve as a reference for other researchers who wish to conduct research on combustion engine performance.
Keywords: engine performance, cyclonic air injector, intake manifold spacer, fuel efficiency, 4-stroke motorcycle